Differential Influence of Demographic Factors on Academic Stress of Higher Secondary School Students of Kerala - Bindu, K. P.; Happy, P. V. (Integrated Journal for Research in Arts and Humanities, 2024)
This descriptive study aimed to find out the differential influence of selected socio-demographic factors like gender, type of family, birth order, socio-economic status and the type of school management on academic stress of higher secondary school students of Kerala. The normative survey method was adopted to collect data from a stratified random sample of 1232 higher secondary school students (Male = 583; Female = 649) by administering the Academic Stress Scale for Secondary School Students and a Personal Data Sheet, both developed by the investigators. The data were analysed by employing independent sample t-test, one way ANOVA and Scheffe's post-hoc test to test five null hypotheses formulated for the study. The result showed that while socio-demographic factors like gender, type of family, birth order, and type of school management has significant differential influence on academic stress of higher secondary school students, the effect of socio-economic status is not significant. Being female student and member of nuclear family are contributory to academic stress among higher secondary school students. The ‘only-child’ experience greater academic stress than the ‘last-born’. The government schools exert lowest academic stress on learners compared to schools in aided and unaided sector.